Alternative lengthening of telomeres confers favorable prognosis in chondrosarcomas - Ji-Yong Sung; Jin-Hong Kim; Yi-Jun Kim (Journal of Translational Medicine)
Abstract Background Cancer cells achieve replicative immortality through telomere maintenance mechanisms (TMMs), primarily via telomerase activation or alternative lengthening of telomeres (ALT). Sarcomas frequently employ the ALT pathway, which traditionally correlates with adverse clinical outcomes. However, chondrosarcomas represent a unique context where the role and prognostic significance of ALT remain largely unexplored. Methods We performed comprehensive analyses of single-cell RNA-sequencing data from patients with chondrosarcoma and integrated this with 90 bulk RNA-seq datasets. This approach enabled detailed characterization of TMM at single-cell resolution, identification of ALT-specific signatures, and evaluation of the tumor microenvironment in chondrosarcomas. Results Patients with ALT-like chondrosarcomas exhibited significantly improved survival compared to those with non-ALT-like chondrosarcomas. Analysis of the tumor immune microenvironment revealed distinct metabolic and immune landscapes between the ALT-like and non-ALT-like groups. Single-cell analysis showed that high-entropy stem-like cells in high-grade chondrosarcomas predominantly adopted telomerase activation over the ALT pathway as their TMM. Additionally, we identified a 100-gene signature that reliably distinguishes ALT-like chondrosarcomas, providing a robust molecular marker for classification and prognosis. Conclusions Our study reveals ALT-like state as a marker of favorable prognosis in chondrosarcomas—contrasting with its typically adverse implications in other sarcomas. We establish a robust 100-gene signature that reliably identifies ALT-like chondrosarcomas and characterize their distinct immune microenvironment profile. Graphical abstract